МОНИТОРИНГ СОСТОЯНИЯ АСИНХРОННЫХ ДВИГАТЕЛЕЙ С ИСПОЛЬЗОВАНИЕМ МЕТОДОВ ТОКОВОЙ ДИАГНОСТИКИ - Арипов, Н.М.; Отажонова, М.К. (SCIENCE and SOCIETY, 2025)
Nowadays, asynchronous motors (AM) are widely used in all areas of production. In order to reduce equipment costs, the development of new methods is relevant for monitoring the state of engines without stopping.
Keywords: asynchronous motor; state monitoring; higher harmonics; Motor Current Signature Analysis (MCSA)